A review: Surveillance of lumpy skin disease (LSD) a growing problem in Asia. (September 2021) - Khan, Yasir Razzaq; Ali, Ahmad; Hussain, Kashif; Ijaz, Muhammad; Rabbani, Ameer Hamza; Khan, Rabia Liaquat; Abbas, Syed Nazar; Aziz, Muhammad Umair; Ghaffar, Awais; Sajid, Hina Afzal
Abstract: Lumpy skin disease (LSD) is a viral disease caused by lumpy skin disease virus (LSDV), a member of Capripoxvirus, genus of Poxviridae family. It is a transboundary infection of monetary significance that primarily affects water buffaloes and cattle. LSD was known to be once endemic in Saharan regions of Africa but later on reported in central Asian and neighboring countries of Pakistan like, India, Iran and China. It is a vector borne disease and arthropods are believed to be the main perpetrators. It is discernible by its high morbidity and low mortality. Characteristic lumps on skin and high fever are considered as major signs while reduced milk production, infertility, early embryonic death and anorexia are some of the salient clinical manifestations of the disease. Additionally, nodules on mucosa of oro-pharynx, udder, genitalia and rectum are usually observed on examination. This article summarizes LSD outbreaks across Asia during last fifteen years. It is a general consensus amongst the veterinary community that disease is endemic in Pakistan as it shares borders with India, Iran and China where recent outbreaks are reported. Historically Pakistan is free of LSD, however it is at high risk of a LSDV outbreak as neighboring regions are becoming endemic. Vaccination, strict quarantine measures, limited movement of livestock along with vector control could be effective for preventing the spread of the disease. This review aims to summarize the latest developments in the epidemiology of LSD with the focus on transboundary spread, possible emergence and economic implications on Pakistan. Highlights: Lumpy skin disease is amongst the major health problems affecting the livestock industry. Endemic and sporadic outbreaks worldwide, especially in Africa and Asia due to its transboundary transmission ability. Susceptible hostscontract the virus principally by mechanical means from hematophagous arthropods. Vaccination combined with other control measures are the most effective way of limiting the spread of disease. Pakistan is currently free from this disease; however, it is at a risk of an outbreak as the disease is in neighbourhood.